Developing a Formative Assessment Protocol to Examine Formative Assessment Practices in the Philippines. Issue 4 (1st October 2020) - Cagasan, Louie; Care, Esther; Robertson, Pamela; Luo, Rebekah
ABSTRACT: This paper explores ways of capturing teachers' formative assessment behaviors in Philippine classrooms through an observation tool. Early versions of the tool were structured using the 'Elicit-Student response-Recognize-Use' ESRU model. To account for the practices observed in the classroom, the observation tool was resituated to focus on Elicit (E) and Use (U) components. Both cultural and physical factors that characterize the Philippine classroom were considered to help ensure that the observation tool would reflect current practices in classrooms. Data from the tool are envisioned to inform the Philippines' Department of Education as they embark on the development of teacher competencies in formative assessment. The final version of the tool captures the basic practices in a reliable way. The tool provides a model of increasing competency in formative assessment implementation that can be used to design teacher training modules and for professional development.